2009
DOI: 10.1007/s10640-009-9268-6
|View full text |Cite
|
Sign up to set email alerts
|

Household Versus Individual Valuation: What’s the Difference?

Abstract: Abstract.Standard practice in stated preference typically blurs the distinction between household and individual responses, but without a clear theoretical or empirical justification for this approach. To date there have been no empirical tests of whether values for say a two adult household elicited by interviewing one randomly selected adult are the same as the values generated by interviewing both adults simultaneously. Using cohabiting couples, we conduct a choice experiment field study valuing reductions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Others have applied similar theories on households, relating choice shift to the property of income pooling (e.g. Munro, 2005;Bateman and Munro, 2009). Finally, environmental economists have similarly invoked a concept of choice shift to question whether individual preferences are robust to aggregation: '[…] group willingness to pay for a project that enhances environmental quality will systematically differ from the sum of individual net benefits' (Howarth and Wilson, 2006: 3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have applied similar theories on households, relating choice shift to the property of income pooling (e.g. Munro, 2005;Bateman and Munro, 2009). Finally, environmental economists have similarly invoked a concept of choice shift to question whether individual preferences are robust to aggregation: '[…] group willingness to pay for a project that enhances environmental quality will systematically differ from the sum of individual net benefits' (Howarth and Wilson, 2006: 3).…”
Section: Introductionmentioning
confidence: 99%
“…Collective induction treatment (Demont et al, 2012) Stated and revealed preference research, experimental auctions Individual versus household valuation (Bateman and Munro, 2009) Democratic theory, deliberative valuation (Sagoff, 1988;Howarth and Wilson, 2006), market stall (MS) approach (Macmillan et al, 2002) Valuation of public goods, environmental economics Figure 1. Epistemological representation of research disciplines and cross-cutting themes connected to the empirical concept of the collective induction treatment…”
mentioning
confidence: 99%
“…A trivial fact, however, once respondents are part of multi-person households it becomes almost impossible to elicit an "uncontaminated" WTP measure that with some degree of confidence can be aggregated over one or the other response unit (e.g. Quiggin 1998;Bateman and Munro 2006). The correct unit will not only depend on how and to whom the WTP question is phrased, but on the respondent's self-perceived agency and the type of resource allocation model prevailing in her 1 household (Delaney and O'Toole 2006;Strand 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The recent findings of Bateman and Munro [2009] and Lindhjem and Navrud [2009] confirm that adult decision makers in a given household react differently to the same choice situation. This is true even when they are asked to answer for the household.…”
Section: Discussionmentioning
confidence: 75%
“…Bateman and Munro [2009] Section II develops the conceptual basis for our evaluation of how dependency relationships among household members may influence responses to stated preference questions describing policy changes that would affect the intensity of that dependency.…”
mentioning
confidence: 99%